Bacteroides genus is associated with lower executive function in cognitively unimpaired participants. (20th December 2022) - Forst, Allison A; Heston, Margo B.; González, Antonio; Chin, Nathaniel A.; Przybelski, Robert J; Johnson, Sterling C.; Asthana, Sanjay; Knight, Rob; Kaddurah‐Daouk, Rima; Rey, Federico E.; Bendlin, Barbara B.
Abstract: Background: Vitamin B1, B6, and B12 deficiencies are associated with increased prevalence of dementia due to Alzheimer's disease (AD). Clinical trials suggest that vitamin supplementation may improve cognitive function, however the mechanisms that link these factors remain unknown. A site of vitamin metabolism and synthesis is the gut microbiome, which is compositionally altered in AD. The gut microbiota's role in perpetuating vitamin deficiencies and subsequent cognitive decline is unclear, so here we tested the hypothesis that lower abundances of vitamin B‐modulating microbes are linked to lower cognitive testing scores. Method: 211 cognitively unimpaired participants were recruited from the Wisconsin Alzheimer's Disease Research Center and Wisconsin Registry for Alzheimer's Prevention (Table 1). Stool samples were collected at home and returned chilled, and 16S rRNA sequencing was performed to characterize gut microbiome composition. QIIME2 was used to denoise ( deblur ) and classify features, and phyloseq ( R ) was used to filter rare taxa, compute relative abundances, and agglomerate at genus rank. Literature review was used to select 10 microbial genera which synthesize/metabolize B vitamins (Table 2). The Rey Auditory Verbal Learning Test (RAVLT) long‐delay recall score and Trail Making Test (TMT) B (number‐letter switching) examined verbal memory and executive function, respectively. Multiple linear regression was conducted on each cognitive outcome to test microbial associations. Result: Higher relative abundance of the B vitamin‐synthesizing genus Bacteroides was associated with greater time to complete the TMT B. This remained significant after controlling for covariates of participant age, sex, and years of education (Table 3). No other genera were significantly associated with either the TMT B or RAVLT scores. Conclusion: In a cognitively unimpaired participant group, Bacteroides was correlated with lower performance on an executive function task. This genus was previously identified as elevated in people with AD and mild cognitive impairment; this study, therefore, indicates a relationship between Bacteroides and executive function even before cognitive decline. Bacteroides species are also linked to inflammation, which may explain the results of the current study. Future work should examine how Bacteroides relates to both biomarkers of neuroinflammation and cognitive function in unimpaired participants.